High Cell Density Perfusion Process of Quail Cells Producing Oncolytic rVSV‐NDV - Lennart Jacobtorweihe; Sven Göbel; Markus Wolschek; Jennifer Altomonte; Udo Reichl; Yvonne Genzel (Engineering in Life Sciences, 2025)
ABSTRACT Oncolytic viruses as agents for the treatment of various types of cancer have demonstrated their potential in many clinical studies over the past decades. In particular, rVSV‐NDV (a recombinant vesicular stomatitis virus [VSV] construct with fusogenic Newcastle disease virus glycoproteins) shows promising preclinical results. This is due to its safety profile, immunostimulatory effects, and efficacy based on strong syncytia formation. Since virotherapy requires a high input of infectious viruses, efficient production processes are needed. Good manufacturing practice (GMP)‐compliant CCX.E10 cells have been previously reported as a high‐titer‐producing rVSV‐NDV candidate in batch mode. Here, semi‐perfusion was used to test quail‐originated CCX.E10 cells for rVSV‐NDV production at high cell densities and in different cell culture media. The best condition was transferred to a full perfusion process in a 3 L bioreactor using a tangential follow depth filtration (TFDF) device for cell retention. The integrated depth filter with a pore size of 2–5 µm allowed 99.9% cell retention at viable cell concentrations (VCCs) of up to 20.6 × 106 cells/mL and continuous virus harvesting. With this setup, we were able to produce 1.33 × 109 TCID50/mL infectious virus with a 5‐fold increase in space‐time yield (STY) compared to a batch process as a control. Practical application: Despite significant progress in oncolytic virus development, early research primarily focuses on viral design and therapeutic potential, often overlooking production challenges until later stages. This gap hinders clinical translation, as manufacturing high oncolytic virus doses (up to 10¹¹ infectious particles per injection) remains a major bottleneck. Implementing GMP‐compliant cell substrates alongside perfusion cultures is essential to overcoming the low yields of traditional batch production. These advancements have far‐reaching implications for reducing costs, increasing dose availability, and accelerating the clinical adoption of this promising immunotherapy.